EMOTIONAL VALUE INFLUENCE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AND CORPORATE IMAGE MODERATION EFFECTS - Conny, Conny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study investigates the roles of emotional value and corporate image as key drivers of customer loyalty in the restaurant sector, while also exploring the mediating and moderating functions of customer satisfaction. Employing a quantitative research design, data were collected through a structured questionnaire using a five-point Likert scale, targeting restaurant customers as respondents. The analytical technique used was Partial Least Squares Structural Equation Modeling (PLS-SEM), which is well-suited for testing complex relationships among latent variables and handling non-normal data distributions. The results indicate that emotional value exerts a strong and positive influence on customer satisfaction, which, in turn, significantly contributes to building customer loyalty. Although corporate image does not directly affect loyalty, it plays an important role in enhancing satisfaction and amplifying its impact on loyalty when acting as a moderating variable. Furthermore, customer satisfaction effectively mediates the relationship between emotional value and loyalty, affirming its central role in shaping consumer behavior. Interestingly, the interaction between corporate image and emotional value did not show a significant effect on satisfaction, suggesting that these constructs operate more independently within this context. Overall, the study highlights the importance of creating emotionally engaging customer experiences and maintaining a strong corporate image to foster satisfaction and long-term loyalty in the competitive restaurant industry landscape